2005
DOI: 10.1007/s10661-005-8223-4
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Monitoring Of Remedial Dredging At The New Bedford Harbor, Ma, Superfund Site

Abstract: New Bedford Harbor (NBH), MA, is a Superfund site because of high polychlorinated biphenyl (PCB) concentrations in the sediment. From April 1994 to September 1995, a remedial dredging operation (termed the "Hot Spot") removed the most contaminated sediments (PCB concentrations greater than 4000 microg/g) from the upper harbor. During remediation, a monitoring program assessed the potential environmental impacts to NBH and adjacent Buzzards Bay. The monitoring program was developed with input from federal, stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 19 publications
4
34
0
Order By: Relevance
“…Within a station over time (b), there is similar natural variability pattern at all stations, primarily due to the mussel reproductive cycle; however, the differences in PCB tissue concentration are maintained over the entire period (note difference in scales among stations) approach was that almost the entire UH, including the Hot Spot area, was to be dredged again during future remedial activities to obtain final PCB cleanup concentrations. An extensive operational water quality monitoring program was implemented to ensure this strategy worked (Bergen et al 2005), and operational water column monitoring has demonstrated that PCBs were not being transported to cleaner areas of the harbor. The LTM data show that the UH PCB sediment concentrations were back to baseline in 1999 (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within a station over time (b), there is similar natural variability pattern at all stations, primarily due to the mussel reproductive cycle; however, the differences in PCB tissue concentration are maintained over the entire period (note difference in scales among stations) approach was that almost the entire UH, including the Hot Spot area, was to be dredged again during future remedial activities to obtain final PCB cleanup concentrations. An extensive operational water quality monitoring program was implemented to ensure this strategy worked (Bergen et al 2005), and operational water column monitoring has demonstrated that PCBs were not being transported to cleaner areas of the harbor. The LTM data show that the UH PCB sediment concentrations were back to baseline in 1999 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…1], several remedial activities have occurred in the subtidal area. The "Hot Spot" remediation removed sediments with PCB concentrations greater than 4,000 ppm and was completed in the fall of 1995 (Bergen et al 2005). Limited dredging occurred between 2000 and 2004, and full-scale dredging to remove "Operable Unit 1" sediments began in 2004 in the UH.…”
Section: Introductionmentioning
confidence: 99%
“…Industrial wastes were discharged directly into the harbor from the 1940s to the 1970s, producing contamination of sufficient magnitude to warrant listing on the US EPA's National Priorities List as a Superfund site (Bergen, Nelson, Mackay, Dickerson, & Jayaraman, 2005; Nelson et al., 1996). Sediment PCB levels near discharge were measured as high as 100,000 Όg/g dry weight (Weaver, 1984), and at other areas of the Superfund site have been measured as 2,100 Όg/g dry weight in NBH (total PCBs) (Pruell et al., 1990), or >10,000 times greater than the sediment guideline value for total PCBs that has been correlated with probable adverse biological effects (180 ng/g dry weight) (Long, Macdonald, Smith, & Calder, 1995).…”
Section: Introduction To the Killifish Story: Rapid Adaptation To Extmentioning
confidence: 99%
“…The ''Hot Spot'' remediation removed sediments with PCB concentrations greater than 4000 ppm and was completed in the fall of 1995 (Nelson and Bergen, 2012;Bergen et al, 2005). The Superfund Site is currently being extensively remediated, and the overall goals of the project are to: (a) reduce the health risks due to the consumption of PCB-contaminated local seafood, (b) reduce the health risks due to contact with the PCBcontaminated shoreline sediments, and (c) improve the quality of the Harbor's highly degraded marine ecosystem (EPA ROD, 1998).…”
Section: Implications Of Pcbs and Other Contaminants In The Yoy Bluefishmentioning
confidence: 99%